Pancasila as the Value of Cultural Diversity in Forming the Character of the Young Generation of Indonesia - Saiful Saiful; Rizal Fahmi (Proceedings of AICS - Social Sciences, 2021)
Value is an abstract concept that is discovered in every human being and becomes extremely significant in every aspect of life. All human activities in daily life are always filled with a variety of values. This is done, of course, by incorporating moral values that are believed to be true, such as those contained in Pancasila, namely, by integrating divine values, human values, values of unity, populist values, and values of justice in various aspects of the younger generation's lives, so that the younger generation of the future will be the young generation of Indonesia with the character following the values contained in Pancasila. The younger generation is a generation that understands the values of human behavior related to God Almighty, oneself, fellow human beings, the environment, and nationality which are manifested in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, regulations. manners, and culture.Keywords: Pancasila, Cultural Diversity, Character, Young Generation.